2021
DOI: 10.1158/1078-0432.ccr-20-2404
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A Mutation May Define an Immunologically Active Subgroup in Patients with Microsatellite Stable Colorectal Cancer

Abstract: Introduction: ARID1A is commonly mutated in colorectal cancer (CRC), frequently resulting in truncation and loss of protein expression. ARID1A recruits MSH2 for mismatch-repair during DNA replication. ARID1A deficiency promotes hypermutability and immune activation in preclinical models but its role in CRC patients is being explored. Methods:The DNA sequencing and gene expression profiling of CRC patients were extracted from TCGA and MD Anderson Cancer Center databases, with validation utilizing external datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 58 publications
0
23
1
Order By: Relevance
“…Additionally, we subsequently focused on investigating genetic alternations and speculating about their potential functions by comparing the somatic mutations between the high- and low-immunity cohorts. Moreover, the results demonstrated that 32 genes mutated differently, which were thought to mainly participate in immunobiological pathways, such as T cell activation, PD-L1-mediated immune escape, and T helper cell differentiation ( Heinonen et al, 2015 ; Shen et al, 2018 ; Li et al, 2019 ; Jung et al, 2021 ; Mehrvarz Sarshekeh et al, 2021 ). Interestingly, some altered genes have the potential to regulate the immunometabolism and neuroinflammation ( Kataria et al, 2019 ; Turner et al, 2019 ; Sheetz et al, 2020 ), which may participate in the metabolic cross-talk between tumor cells and surrounding immune-infiltrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we subsequently focused on investigating genetic alternations and speculating about their potential functions by comparing the somatic mutations between the high- and low-immunity cohorts. Moreover, the results demonstrated that 32 genes mutated differently, which were thought to mainly participate in immunobiological pathways, such as T cell activation, PD-L1-mediated immune escape, and T helper cell differentiation ( Heinonen et al, 2015 ; Shen et al, 2018 ; Li et al, 2019 ; Jung et al, 2021 ; Mehrvarz Sarshekeh et al, 2021 ). Interestingly, some altered genes have the potential to regulate the immunometabolism and neuroinflammation ( Kataria et al, 2019 ; Turner et al, 2019 ; Sheetz et al, 2020 ), which may participate in the metabolic cross-talk between tumor cells and surrounding immune-infiltrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of immunotherapy, some systemic in ammatory markers (such as NLR, PLR, CRP, albumin, etc) have been found to be closely related to the prognosis of ICIs in different kinds of tumors (Dharmapuri et al 2020;Formica et al 2020;Rossi et al 2020). ARID1A mutation has been reported as an independent predictor of longer PFS during tumor immunotherapy (Okamura et al 2020), and is closely related to increased expression of gene signatures of immune checkpoint, cytotoxic T-cell function and antigen presentation(Mehrvarz Sarshekeh et al 2021). Increased expression of key genes (HAVCR2, IDO1, IL4I1, LAG3, PDCD1, PDCD1LG and THFRSF4) which are known to be related to immune response are also associated with ARID1A mutation(Mehrvarz Sarshekeh et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A mutation has been reported as an independent predictor of longer PFS during tumor immunotherapy (Okamura et al 2020), and is closely related to increased expression of gene signatures of immune checkpoint, cytotoxic T-cell function and antigen presentation(Mehrvarz Sarshekeh et al 2021). Increased expression of key genes (HAVCR2, IDO1, IL4I1, LAG3, PDCD1, PDCD1LG and THFRSF4) which are known to be related to immune response are also associated with ARID1A mutation(Mehrvarz Sarshekeh et al 2021). In our study, we found loss of ARID1A protein was associated with lower albumin (p=0.0064) and low ARID1A mRNA was associated with higher PLR (p=0.0689).…”
Section: Discussionmentioning
confidence: 99%
“…Previous preclinical and clinical studies have reported that ARID1A mutation can enhance the immunogenicity of tumor cells in breast cancer ( 107 ) and improve tumor sensitivity to immune checkpoint inhibitors in various cancers, including metastatic urothelial cancer ( 108 ), advanced nonsmall cell lung cancer ( 109 ), ovarian clear cell cancer ( 110 ), colorectal cancer ( 111 , 112 ), gastrointestinal cancer ( 113 ), and colon cancer ( 114 ), which can provide insights into ARID1A-mutated breast cancer. Meanwhile, ATM inhibitors and HDAC6 inhibitors can further potentiate the efficacy of antitumor immunity in ARID1A-mutated ovarian cancer ( 115 , 116 ).…”
Section: Promising Treatment Targetsmentioning
confidence: 99%